Perceptions of Accredited Social Health Activists on Depression: A Qualitative Study from Karnataka, India - Mary Kapanee, Aruna Rose (Indian J Psychol Med, 2018)
BACKGROUND: Depression is a significant public health concern in India, associated with a large treatment gap. Assessing perceptions of Accredited Social Health Activists (ASHAs) on depression can be invaluable as they are selected to work at the interface between their own communities and the health-care delivery system. AIMS AND OBJECTIVES: This study aimed at utilizing a qualitative approach to examine the ASHAs’ understanding of depression, their mental health-care practices specific to depression, and their capacity-building needs with regard to identification and helping persons with depression. SUBJECTS AND METHODS: A cross-sectional qualitative study using two focus group discussions was conducted. The sample comprised 14 ASHAs in the age range of 25–45 years from Bengaluru urban district. The data were analyzed manually by the method of directed content analysis. RESULTS: The ASHAs were found to have inadequate knowledge of the signs and symptoms of depression, its biopsychosocial nature, and its impact on functioning. Causation of depression was narrated in terms of psychosocial stressors. The majority expressed the need for primarily psychosocial interventions for depression. All participants reported their motivation to obtain training in identifying persons with depression and providing simple psychosocial intervention for them. CONCLUSION: This study indicates that ASHAs have poor knowledge of depression, which could be leading to its low recognition and treatment in the communities they work in. They are therefore likely to benefit from capacity building on depression which includes familiar nomenclature, biopsychosocial elucidation of the illness, life-span approach, understanding of its impact on various domains of functioning, and the treatments available.